Changes to coral health and metabolic activity under oxygen deprivation - Murphy, James WA; Richmond, Robert H (PeerJ PrePrints, 2016)
Scleractinian corals play a critical role in tropical marine ecosystems by providing essential structure and food for coral reef inhabitants. However, recent investigations have found an alarming increase in coral losses from a variety of stressors, which threatens the general health and resilience of tropical coastal ecosystems. The effect of oxygen deprivation on the health of Hawaiian corals based on local drivers is of particular concern. On Hawaiian reefs, the fast-growing, invasive algae Gracilaria salicornia overgrows coral heads, restricting water flow and light, thereby smothering corals. Field data shows hypoxic conditions (dissolved oxygen (DO2) < 2 mg/L) occurring underneath algal mats at night, and concurrent bleaching and partial tissue loss of shaded corals. This study evaluates changes in coral health and metabolism through the replication of hypoxic conditions in a laboratory setting in order to limit the contribution of additional environmental variables to health shifts. Analyses of metabolic stress were accomplished through the quantification of lactate dehydrogenase and opine dehydrogenase activities. Through experimentation, treatment corals were observed to exhibit significant increases in alanopine and strombine dehydrogenase activities (ADH and SDH, respectively), but little to no lactate or octopine dehydrogenase activity. These findings indicate that not only is hypoxia a major source of increased coral stress, which occurs in response to invasive algae mat smothering, but provide novel insight into coral metabolic shifts in extremely low-oxygen environments and point to ADH and SDH as possible tools for hypoxia mitigation.
Keywords: Montipora capitata; anoxia; hypoxia; enzyme activity; alanopine dehydrogenase; strombine dehydrogenase; ecological resilience; coral metabolism; corals; Hawaii